Professores iniciantes do estado de Minas Gerais e as possibilidades de constituição de comunidades colaborativas de desenvolvimento profissional docente - Silva, Cleunice Cristina da (2023)
The aim of this research was to investigate possible initiatives to welcome and support beginning teachers working in state schools in Minas Gerais, given that there are many reasons why professionals drop out and give up in their first years of teaching, such as the feeling of loneliness and not belonging, the lack of support associated with the precariousness and devaluation of their careers, and the challenges encountered during their initiation into teaching. A quantitative-qualitative, descriptive, and exploratory study was carried out using questionnaires sent to 46 Regional Teaching Superintendencies in Minas Gerais and interviews with 10 beginning teachers (9 contracted and 1 permanent) among those who answered the questionnaires. The study addressed the challenges faced by these teachers and explored how a collaborative learning community can contribute to the adaptation and development of these professionals during their professional integration. It also investigated the existence of strategies and initiatives for welcoming and providing emotional and professional support within the network, as well as the impact of the collaborative community on the professional success of novice teachers. It is hoped, therefore, that this research will effectively contribute to a change in professional reality, proposing the possibility of implementing a teaching-learning community from the perspective of professional development in an attempt to welcome and accompany teachers in their first years of teaching so that they can start their careers more lightly and with the prospect of professional continuity.